Characterization of airborne bacterial diversity in conventional hen houses, enriched colonies and aviaries, and link between possible bioaerosol sources - M.-W. St-Germain; M. Veillette; V. Létourneau; A.D. Larios Martínez; S. Godbout; M. Boulianne; C. Duchaine (Poultry Science, 2025)
Background: Canada’s transition toward alternative housing systems for laying hens may have an impact on bioaerosol content and concentrations in those environments. This project aimed to characterize the airborne bacterial diversity in six conventional hen houses, six enriched colonies and six aviaries. The bacterial diversity found in bioaerosols was also compared to the diversity found in feces or litter samples from each corresponding housing type to investigate similarities between possible bioaerosol sources and bioaerosols. Results: Specific richness (Sobs) and CHAO1 indexes were higher in air samples from conventional hen houses and enriched colonies, compared to their corresponding fecal or litter samples, which was not the case for aviaries samples. No significant differences were found between the Shannon and inverse Simpson (InvSimpson) indexes of air samples, compared to their corresponding fecal or litter samples. Firmicutes were the dominant phyla in all samples, followed by Actinobacteria. Dominant genera were Lactobacillus, unclassified Lanchnospiraceae, unclassified Actinomycetales, unclassified Clostridales and unclassified Ruminococcaceae. OTUs (Operational Taxonomic Units) were associated with hen microbiota and gut microbiota, and soil. Homogeneity of molecular variance analyses (HOMOVA) revealed significant differences between air samples from aviaries, compared to air samples from conventional and enriched cage houses. Significant differences were found between air and fecal or litter samples from conventional hen houses and enriched colonies, but not among aviary samples. Conclusions: Findings highlight the effects of housing types on airborne bacterial diversity, and similarities in bacterial diversity between air and fecal or litter samples from three types of husbandry. Most dominant OTUs were shared across all samples, but were different in proportions, which may account for the differences in alpha and beta diversities. The overlap in bacterial diversities between air and litter samples collected in aviaries brings out the contribution of litter to ambient bioaerosols.